Anticancer and Antimicrobial Activities of Naproxen and Naproxen Derivatives - Han, M. İhsan and Küçükgüzel, Ş. Güniz (Mini Reviews in Medicinal Chemistry, 2020)
This review explains the effects of naproxen and the naproxen moiety in important biological activities. Naproxen, 2-(6-methoxynaphthalen-2-yl)propionic acid, is one of the most utilized propionic acid derivatives to the cure of many injuries or pains. Naproxen is a non-steroidal antiinflammatory drug (NSAID), which is generally used among the NSAIDs. Even though it has gastrointestinal side effects, naproxen has been safely used for many years because of the good cardiovascular sight. In the past years, except for anti-inflammatory effects, other pharmacological activities of naproxen, especially anticancer and antimicrobial activities, gain the attention of researchers. Naproxen shows its activity by inhibiting the COX-2 enzyme. There is significant interest in the possibility that COX-2 inhibitors might retard or prevent the development of various cancer types, which is often characterized by COX-2 expression. The activities of both naproxen and new molecules derived from naproxen were frequently investigated.
Keywords: anticancer